ANALISIS KETAHANAN PANGAN DAN KESEJAHTERAAN PETANI BERBASIS PRODUKSI SORGUM PADA LAHAN MARGINAL DI LOMBOK TIMUR - Haryati Ningsih, Dwi; Ashari, Ria (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2025)
Food security is an effort to fulfill basic food needs. Therefore, local food production, specifically sorghum, needs to be increased to enhance national food diversification. Sorghum is one of the agricultural commodities with potential for cultivation as an alternative food source besides rice and corn. The purpose of this study is to determine the level of local food security for sorghum and the welfare level of sorghum farmers in Jerowaru District, East Lombok Regency. The research was conducted in Pemongkong Village, Jerowaru District, East Lombok Regency. The tool used in the research was a questionnaire with a sample size of 30 respondents. The research area was determined deliberately (Purposive Method) with sampling techniques using random sampling. To measure the welfare level of sorghum farmers, a 5-point Likert scale was used, which was then scored using the composite method. The IKP (Food Security Index) per hectare was 1.28, indicating that sorghum production per hectare is more than sufficient to meet the family's food needs. An IKP greater than 1 suggests that the family's food security can be met or even exceed their basic needs. However, while the IKP indicates food sufficiency for the family, the Food Security Ratio (RKP), calculated from the ratio between KP and the total food needs across all food types (rice, maize, sorghum), shows a lower value. For per hectare, the RKP is only 0.25, which means that sorghum production can only fulfill about 25% of the total food needs that include rice, maize, and sorghum. Overall, the average composite score for all indicators of sorghum farmers' welfare level is 0.61, which falls into the High category. This indicates that in general, the performance of the various indicators is quite good, although some aspects, such as business security and farmer skills, require more attention for improvement.